Darmmikrobiota und Autismus-Spektrum-Störungen: ein Überblick zu Zusammenhängen und möglichen Implikationen für therapeutische Interventionen : Übersichtsarbeit - Neubauer, Johanna Charlotte; Kaiser, Anna; Hohmann, Sarah (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2024)
At the beginning of research on microbiota, researchers focused mainly on the role of microbiota dysbiosis in the development of gastrointestinal diseases. However, over the last years, researchers have also identified correlations with other physical processes and neuropsychiatric diseases such as autism spectrum disorder. These correlations are believed to be at least partly mediated through the brain-gut-microbiome axis. An altered composition of microbiota in patients with autism spectrum disorder was detected compared to healthy controls. Today, the discussion centers around a possible systemic impact of the metabolites of some microbiota or microbiota-induced chronic inflammatory processes on the brain (mediated through the brain-gut-microbiome axis) as an underlying mechanism. Still, the specific underlying mechanisms remain largely unknown, so conclusions on therapeutic implications are difficult to determine. Here, we describe some promising approaches to improving autistic behavior through dietary changes, the use of prebiotics and probiotics, stool transplantation from healthy controls, and restricted absorbance of certain metabolites. We need further clinical studies of high quality to fully understand the pathophysiology of autism spectrum disorder and to improve diagnostic and therapeutic strategies.